The effect of total cost of ownership on customer perceived value during industrial buyer decision making process: an investigation in truck market - Cengiz, Yeliz (My University, 2019)
Bu çalışma kapsamında, endüstriyel satın alma sürecinde kamyon sektörü özelinde sahipliğin toplam maliyetinin müşterinin algıladığı değer üzerindeki etkisi araştırılmıştır. Araştırmada öncelikle endüstriyel satın alma, sahipliğin toplam maliyeti ve müşterinin algıladığı değer konuları incelenmiştir. Ardından müşterilerin algılarını ölçmek üzere bir anket formu hazırlanmıştır. Sahipliğin toplam maliyetini ölçmek üzere, Ferrin ve Plank (2002) tarafından yapılan çalışmadan faydalanılarak 54 maddelik bir ölçek meydana getirilmiştir. Müşterinin algıladığı değeri ölçmek üzere, Dwivedi, Merrilees, Miller ve Herington (2012) tarafından geliştirilen 12 maddelik ölçek kullanılmıştır. Yapılan analizler sonucunda sahipliğin toplam maliyetinin beş faktörlü, müşterinin algıladığı değerin tek faktörlü bir yapıya sahip olduğu tespit edilmiştir. Hipotez testleri neticesinde ise, sahipliğin toplam maliyetinin müşterinin algıladığı değeri pozitif ve anlamlı şekilde etkilemekte olduğu saptanmıştır. Ayrıca katılımcıların ölçeklere verdikleri yanıtların da çeşitli demografik özelliklere göre farklılaştığı bulgusu elde edilmiştir.

Within the scope of this study, the effect of total cost of ownership on customer perceived value during industrial buying process in truck market was investigated. In the research firstly the literature about the topics of industrial buying, total cost of ownership and customer perceived value were reviewed. Then, a survey questionnaire was prepared to measure the perceptions of the customers. In order to measure total cost of ownership, a scale with 54 items was composed via benefiting from the study of Ferrin and Plank (2002) was used. Moreover, in order to measure customer perceived value, the scale with12 items developed by Dwivedi, Merrilees, Miller and Herington (2012) was used. After factor analyses, it was found that total cost of ownership has five factors, and customer perceived value has only one factor. According to the results of hypothesis tests, it was found that total cost of ownership affects customer perceived value positively and significantly. Moreover, it was found that the answers of participants to the scales are different according to some demographic features of the respondents.
Keywords: Customer Perceived Value; Decision Making; Endüstriyel Satın Alma; Industrial Buying; Kamyon Total Cost of Ownership; Karar Verme; MüşterininAlgıladığı Değer; Sahipliğin Toplam Maliyeti; Truck